Evaluation of optimal operation alternatives of reactors used for d‐glucose oxidation in a bi‐enzymatic system with a complex deactivation kinetics. Issue 1 (14th May 2014) - Maria, Gheorghe; Crisan, Mara
Abstract One essential engineering problem when developing an industrial enzymatic process concerns the choice of the reactor alternative based on a priori knowledge on process and (free vs immobilized) enzyme characteristics, materials, and operation costs. For a multi‐enzymatic system, involving complex interactions among enzymes that exhibit optimal activity on different parametric domains and a high‐order deactivation, this problem requires an extended analysis. The study aims at extending the use of a modular simulation platform by approaching the optimization of complex multi‐enzymatic systems. An optimal constructive and operating alternative is determined for the case study of the complex oxidation of d‐glucose to 2‐keto‐d‐glucose in the presence of oxygen 2‐oxidoreductase (P2Ox, EC 1.1.3.10) and catalase (EC 1.11.1.6), by comparatively analyzing various enzymatic reactor models (simple batch, batch with intermittent addition of enzyme, semi‐batch reactor, continuously operated packed‐bed column, or mechanically agitated reactor with enzyme immobilized on support). Optimal reactor choice is based on the minimum amount of required P2Ox that ensures an imposed reaction conversion and reactor productivity under various technological constraints, by testing two temperatures (25 and 30 °C) and various catalase/P2Ox ratios (0–300/1 U U−1). © 2014 Curtin University of Technology and John Wiley & Sons, Ltd.